Sustainable Water Management Index, SWaM_Index. Issue 1 (1st January 2019) - Maiolo, M.; Pantusa, D.
Abstract: The present paper describes the Sustainable Water Management Index, SWaM_Index, useful for managers to measure the sustainability of water management and to assess the effects of the policies undertaken in the direction of sustainability. The structure of the proposed index has been derived from European legal framework of the water resources sector, and the index is obtained from elementary indicators of environmental, economic, social and institutional nature, subsequently aggregated in sub-themes, themes and pillars. The index is well applicable on a national, regional but also local scale and the sustainable management of water resources is assessed considering natural systems, artificial systems and socio-economic and institutional aspects.